TANTANGAN IMPLEMENTASI KERJASAMA ANTI- TERORISME ANTARA INDONESIA DAN AUSTRALIA TAHUN 2007-2016 - Nala Nourma Nastiti; Yuswari Octonain Djemat; Indah Dwiprigitaningtias (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2017)
The impact of this terrorism incident has been felt by Indonesia and Australia. Although Australia has never experienced direct terrorist attacks in the country, Australia as an ally of the United States is trying to tighten the country's security. Australia and Indonesia are committed to fighting against terrorism explicitly through bilateral anti-terrorism agreements and cooperation. This is strengthened after the Bali bomb attacks I and II that cause casualties Australians. So in addition to the close georgraphical reasons between the two countries, Australia considers Indonesia as a strategic partner to maintain security. With the Lombok agreement in 2006 the beginning of the intensity of cooperation between Indonesia and Australia in combating terrorism. This is enhanced by continued agreements that are continually renewed by both countries. But along with the development of the era of globalization, the effort raises a variety of challenges that can then be analyzed, so that can implement efforts to combat terrorism will be the maximum amid the challenges and obstacles encountered until 2016.